Students perceptions regarding the third year nursing ethics module at Shifa College of Nursing, Islamabad, Pakistan - Khan, Farida Himat (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2013.